Drought and shifts in agropastoral coping strategies in Uganda’s cattle corridor - Mbaziira, J.; Bamutaze, Y.; Egeru, A.; Lein,B H.; Nakakaawa,C.; Mugagga, F.; Nakilezaa, B. (African Journal of Rural Development, 2022)
ABSTRACT Changing climatic conditions including drought and severe dry spells are major challenges to agropastoral food production. The frequency and intensity of prolonged dry-seasons impact agropastoral livelihoods especially crop production. Households cope with these impacts using purposeful and incidental strategies. However, the associated impacts of droughts in relation to shifts in agropastoral purposeful coping strategies is partially explored. Using cross-sectional data of 426 households, and total mean monthly rainfall of 1991-2020, this study examined how seasonal shifts and deficits in rainfall cause shifts in the short-term purposeful coping strategies among agropastoral communities. Results elicit three key findings: (i) agropastoral areas have high annual mean and seasonal rainfall variations, (ii) there is a very strong relationship between shifts in household coping strategies and annual rainfall deficits, and (iii) shifts in coping strategies demonstrate an inverse relationship with households coping behaviors. Findings from the current study provide a basis for an in depth longitudinal survey to reveal the association between frequency and severity of use of these coping strategies in agropastoral communities. The resulting information could then be used to provide locals with solution of purposeful coping strategies that enhances food security.